Evaluasi Penggunaan Antibiotik Pada Pasien Demam Tifoid Anak Di Instalasi Rawat Inap Rsau Adi Soemarmo - Saputri, Ika Sutra Perwirahayu Aji AJI, Zakky Cholisoh, Ph.D.,Apt (2016)
Typhoid fever is an endemic disease caused by Salmonella typhi that infects the gastrointestinal tract, resulting in inflammation of the small intestine and the intestinal lumen. In Indonesia, cases of typhoid fever occur most commonly in children aged 3-19 years. Generally, clinical symptoms are fever, nausea, vomiting, and abdominal pain. The purpose of this study is to evaluate of antibiotics for children with typhoid fever in Inpatient RSAU Adi Soemarmo based on the Pedoman Pelayanan Medis Ikatan Dokter Anak Indonesia (2009) and Panduan Praktik Klinis Bagi Dokter di Fasilitas Pelayanan Kesehatan Primer (2014) by evaluating the right indication, right patient, right drug, and right dose. This research conducted non-experimental method by retrospective data collection. The data were analyzed descriptively to obtain whether the antibiotic prescription, for children with typhoid fever inpatient RSAU Adi Soemarmo are in accordance with right indication, right patient, right drug of choice, and right dose parameters. Antibiotic for typhoid fever used in RSAU Adi Soemarmo is mostly ceftriaxone (30,56 %). The results of this study points out that antibiotic prescription were 100% right indications; 88,9% right patients; 41,67% right drug; and 0 % right dose. Keywords: typhoid fever, antibiotics, right indications, right patient, right drug, right dose.